Desenvolvimento e Avaliação de um Reator Eletrolítico Fotovoltaico para a Produção de Gás Hidrogênio - Rottava, Willian (2016)
This work aimed to develop and evaluate an electrolytic reactor system for the production of hydrogen gas by applying an electromotive force from solar energy. Solar energy is converted into electrical energy through photovoltaic panels and the method of electrolysis was generated hydrogen gas. To carry out the work, different electrodes and electrolytes were tested to determine the best combination to be applied in the reactor on a pilot scale. Developed an electrolytic reactor with unipolar electrodes and graphite using formic acid electrolyte with added glycerol. After a series of tests, the graphite electrode was chosen primarily for its ease of acquisition and use, and also due to the good performance. The electrolyte with higher hydrogen production using graphite was added formic acid with glycerol at 40 °C, with the addition of 0,1% glycerol at 25 °C gave a 313,2% increase in hydrogen production compared to using only formic acid